2009
DOI: 10.1007/s12663-009-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the maxillary sinus according to area of the medial antral wall: a comparison of two ethnic groups

Abstract: The area of the medial wall is related to ethnic/gender groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It also facilitated the correlation between these anatomical compartments and the different ethnic groups relative to climate variations. However, the large dose of ionizing radiation delivered by medical CT is crucial and debatable [19–21] .…”
Section: Introductionmentioning
confidence: 99%
“…It also facilitated the correlation between these anatomical compartments and the different ethnic groups relative to climate variations. However, the large dose of ionizing radiation delivered by medical CT is crucial and debatable [19–21] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study by Maddux and Butaric (2017) found that the relative anteroposterior positioning of the MS apex varied independently of size, being more closely associated with aspects of lateral facial morphology. Similarly, a study by Fernandes et al (2009) found no association between MS volume and aspects of MS shape related to the degree of sinus wall convexity, suggesting considerable idiosyncratic variability may exist in the curvature of the encapsulating walls of the sinus.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, this long historical focus on MS volume has led to a continued research emphasis on volume, despite the availability of imaging modalities permitting reliable quantification of MS shape and surface area (see Butaric & Maddux, 2016 for a review). Still, a few studies have attempted to assess variability in MS shape (Anagnostopoulou et al, 1991; Fernandes et al, 2009; Kim et al, 2002; Lee et al, 2008; McDonnell et al, 1992). For example, Anagnostopoulou et al (1991) investigated variation in overall MS shape using a four‐stage categorization system, while a later study by Kim et al (2002) employed an alternative six category scheme.…”
Section: Introductionmentioning
confidence: 99%
“…They resemble a quadrilateral pyramidal cavity extending into the bodies of the maxilla [ 21 , 22 ]. Lee et al [ 23 ] showed that there was a significant difference along gender and ethnic lines in maxillary sinus volume but there was very little difference in the shape of the maxillary sinus. The sinus appears to preserve a parabolic-hyperbolic shape despite quite marked variations in volume.…”
Section: Discussionmentioning
confidence: 99%